Implementation of Tolerance Values in Islamic Religious Education Learning at UPT SD Negeri No. 03 Lubuk Cuik Batubara - Ade Synta; Bahtiar Siregar (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to analyze the implementation of tolerance values ​​in Islamic Religious Education learning at UPT SD Negeri 03 Lubuk Cuik. The research method used is descriptive qualitative with a phenomenological approach. Data collection techniques use observation, interviews, and documentation. Data analysis techniques through the stages: data condensation, data presentation, and drawing conclusions and verification. The results of the study indicate that the implementation of religious tolerance values ​​is carried out in an integrated manner in the planning, implementation, and evaluation of learning. Islamic Religious Education teachers use a contextual approach and discussion methods, case studies, and value reflections to internalize attitudes of respecting differences, empathy, and peaceful coexistence. Material on commendable morals, stories of the prophets, and students' social experiences are used as a means to develop understanding and awareness of the importance of tolerance. The main supporting factors in this implementation are teacher commitment, principal support, and a school environment that is open to diversity. Meanwhile, the inhibiting factors include time constraints, lack of teacher training on multicultural education, and parents' perceptions that are still less open to differences. The implications of the results of this study indicate that Islamic Religious Education teachers need to continue to be encouraged to use active and contextual learning methods so that the values ​​of tolerance are easier for students to understand and internalize.